Una mirada a la sociología en Medellín: Jornada de Análisis de la sociología en Medellín (2004)
ABSTRACT: By the beginning of the sociology in Medellin, it’s about a program with a strong content of Catholic social doctrine guided by the self-taught sociology, mostly lawyers and some priests trained in Europe, not necessarily sociologists who, from different ideological perspectives contributed to the awareness of the plight of the most vulnerable social sectors. This germ, coupled with the general situation of social crisis which has prevailed both in the country and in Latin America and the rise of revolutionary movements in several countries of the continent, were driving to the linking of many students of this program with social struggles every time More radical and internally great pressure towards changing the curriculum and toward participation in the university.